Analisis Potensi Sektor Pariwisata Di Provinsi Lampung Dengan Pendekatan Location Quotient (LQ) - Yanto, Nana Putri; Ammaru, Faishal Zaky Al (Jurnal Ilmu Ekonomi JIE, 2024)
This study uses the Location Quotient (LQ) approach and Klassen Typology to examine Lampung Province's tourism potential. The goal is to discover economic sectors with growth potential, increase tourism's position in the province's economy, and contribute to the advancement of tourist science. According to an LQ analysis of the Gross Regional Domestic Product (GRDP) from 2015 to 2020, Pringsewu Regency, Bandar Lampung City, and Metro City are prospective bases in the lodging, food and beverage, information, communication, and property sectors. Pesisir Barat Regency demonstrates potential in two fundamental areas and one non-basic one. This study is designed to inform policymakers, researchers, and stakeholders about the sustainable expansion of the Lampung Province tourism sector and further contributions to tourism.